Pengaruh Indikator Risk Based Bank Rating Terhadap Kinerja Keuangan Pada Perusahaan Perbankan yangTerdaftar di BEI Tahun 2012-2016 - Sukma Kartika Dewi, Ni Wayan; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p09, 2019)
The population in this study were 43 Banking Companies listed on the Indonesia Stock Exchange in 2012-2016. Determination of samples in this study using purposive sampling method. Number of Banking Companies that meet the criteria of 6 companies with 30 observations. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially non-performing loans, loan to deposit ratio, capital adequacy ratio have a negative effect on financial performance, and net interest margin has a positive effect on financial performance. While good corporate governance does not affect financial performance. The results of this study are expected for banking companies to pay attention and manage variables that have a negative effect on financial performance. For investors, the results of this study can be used as useful considerations for making investment decisions, especially in assessing financial performance of banks. Keywords: financial performance, risk based bank rating indicator